2014
DOI: 10.3389/fncel.2014.00352
|View full text |Cite
|
Sign up to set email alerts
|

The pivotal role of astrocytes in an in vitro stroke model of the blood-brain barrier

Abstract: Stabilization of the blood-brain barrier during and after stroke can lead to less adverse outcome. For elucidation of underlying mechanisms and development of novel therapeutic strategies validated in vitro disease models of the blood-brain barrier could be very helpful. To mimic in vitro stroke conditions we have established a blood-brain barrier in vitro model based on mouse cell line cerebEND and applied oxygen/glucose deprivation (OGD). The role of astrocytes in this disease model was investigated by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 66 publications
4
62
0
Order By: Relevance
“…In addition, activated MMPs were also deposited in and around blood vessels. Notably, negligible MMP activation was observed in astrocytes (Figure 6C), suggesting proteolytic activation of MMP-9 following release from astrocytes (Maddahi et al, 2009; Neuhaus et al, 2014). As expected, n-3 PUFA treatment dramatically suppressed the extensive activation of MMPs in the brain parenchyma at the same time point (Figure 6B and 6C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, activated MMPs were also deposited in and around blood vessels. Notably, negligible MMP activation was observed in astrocytes (Figure 6C), suggesting proteolytic activation of MMP-9 following release from astrocytes (Maddahi et al, 2009; Neuhaus et al, 2014). As expected, n-3 PUFA treatment dramatically suppressed the extensive activation of MMPs in the brain parenchyma at the same time point (Figure 6B and 6C).…”
Section: Resultsmentioning
confidence: 99%
“…36 As shown in Figure 2, HUVECs and C6 cells treatment with free DOX displayed DOX fluorescence in cytoplasm after 0.5 h, and the fluorescence was distributed in nucleus within a short period of 2-4 h. In comparison, the red fluorescence was observed after 0.5 h and enhanced in nuclei after incubation with DOX/GM1. There was no significant difference in fluorescence intensity between 2-h and 4-h incubation.…”
Section: In Vitro Cellular Uptake Studymentioning
confidence: 87%
“…These findings are consistent with the kinetics of BBB disruption in rodent models of stroke. Indeed, a number of studies have shown that BBB hyperpermeability occurs as early (2–4 hours) after ischaemia and is sustained up to 72 hours later . Moreover, previous OGD studies using bEnd.3 cells have shown paracellular hyperpermeability to occur in response to 2–3 hours of OGD exposure …”
Section: Discussionmentioning
confidence: 99%